Effect of Increasing Degradable Nitrogen from Adding Urea to the Ration of Awassi Ewes in Milk Yield and some Components - Al-Hafz Maher; Mohammed W. M. Ali (Mesopotamia Journal of Agriculture, 2019)
This experiment conducted at 1/12/2017 to 4/3/2018 by using 30 ewes with their lambs. The weights of the ewes between (46-51) Kg and the ages between (3-5) years, to study the effect of increasing degradable Nitrogen from adding urea to the food of Awassi ewes milk yield and components. The experiment done by three levels of Nitrogen degradable (low, 0% urea) (mid, 0.75% urea), (high, 1.5 urea). and by three treatments each of them consists of 10 ewes. The results indicated a significant increase (p≤0.05) in weekly, monthly and commercial yield for the treatment of high degradable protein. For the milk components during sucking and after weaning (fat, protein, lactos, S.N.F) the results revealed non significant differences. The adding of urea to the ration of awassi ewes in creased milk production.